(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2016)
In this study it is aimed to define the teaching, social and cognitive presence perceptions Community of Inquiry Components (CoI) students in simultaneous online learning environments. During the practically continuing 14 weeks, courses were presented over Adobe Connect web conferencing system. In the research analyzes were performed by using the quantitative data that was collected properly for cross-sectional survey model. The participants of research consist of 40 students who are 4th grade students at Computer and Instructional Technologies Department, Distance Learning Program. According to research results; at online teaching held simultaneously; the average of materials intended for teaching presence perception (X=3.14), the average of materials intended for cognitive presence perception (X=3.03) and the average of materials intended for social presence perception(X=3.01) all three were generally higher than the midpoint and all were resulted as "Agree". When the relationship level among presences is examined, on one hand a meaningful relationship at medium level occurs between cognitive-social presences and cognitive-teaching presences on the other hand a meaningful relationship at medium level occurs between social and teaching presences. In this context, it is considered that the results obtained in this study can contribute to online learning environment designers for learning environments and activities which will be prepared by considering individuals in the learning environment and communication environment.